The cyclical behaviour of Islamic bank financing / Mohd Afandi Abu Bakar - Mohd Afandi, Abu Bakar (2014)

(untitled)
This study aims to examine the claim on Islamic banking offers a more stable financial environment as opposed to their conventional counterparts, from the dimension of their financing behaviour. Business cycle theories suggest that one of the factors that lead to the instability is banks’ lending behaviour that tends to over-lend during the booming period and restrict lending during recession. Islamic finance principles work differently, where banks, while could capitalise the opportunity to lend during the booming period, cannot ignore the need to build up the provision for bad and doubtful financing as the financing increases. This helps to moderate the financing growth of booming period. Employing an unbalanced panel data analysis onto global Islamic banks, the findings suggest that the growth of Islamic bank financing is independent of the growth of business cycle indicators. Even when analysed on the fixed rate financing the results hold, suggests that even if the modes of financing is akin to their conventional counterparts, Islamic bank fixed rate financing behaviour is distinct from the conventional ones. In addition to that, an examination of bank provision provides empirical support that Islamic banks do build up contingency reserves accordingly following growth of financing. Collectively, these empirical evidences suggest that where financing behaviour is concerned, Islamic banks are able to offer an economic environment that is more stable. Although the evidence did not claim that their operations are counter-cyclical, but their financing growth is independent of the business cycle. Besides, Islamic banks do practice in building up enough provisioning to support their financing growth.